2017 American Heart Association Focused Update on Pediatric Basic Life Support and Cardiopulmonary Resuscitation Quality: An Update to the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care. Issue 1 (2nd January 2018) - Atkins, Dianne L.; de Caen, Allan R.; Berger, Stuart; Samson, Ricardo A.; Schexnayder, Stephen M.; Joyner, Benny L.; Bigham, Blair L.; Niles, Dana E.; Duff, Jonathan P.; Hunt, Elizabeth A.; Meaney, Peter A.
Abstract : This focused update to the American Heart Association guidelines for cardiopulmonary resuscitation (CPR) and emergency cardiovascular care follows the Pediatric Task Force of the International Liaison Committee on Resuscitation evidence review. It aligns with the International Liaison Committee on Resuscitation's continuous evidence review process, and updates are published when the International Liaison Committee on Resuscitation completes a literature review based on new science. This update provides the evidence review and treatment recommendation for chest compression–only CPR versus CPR using chest compressions with rescue breaths for children <18 years of age. Four large database studies were available for review, including 2 published after the "2015 American Heart Association Guidelines Update for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care." Two demonstrated worse 30-day outcomes with chest compression–only CPR for children 1 through 18 years of age, whereas 2 studies documented no difference between chest compression–only CPR and CPR using chest compressions with rescue breaths. When the results were analyzed for infants <1 year of age, CPR using chest compressions with rescue breaths was better than no CPR but was no different from chest compression–only CPR in 1 study, whereas another study observed no differences among chest compression–only CPR, CPR using chest compressions with rescue breaths, and no CPR. CPR using chest compressions with rescue breaths should be provided for infants and children in cardiac arrest. If bystanders are unwilling or unable to deliver rescue breaths, we recommend that rescuers provide chest compressions for infants and children.